INVESTIGATING FACTORS AFFECTING THE QUALITY OF E-LEARNING AT ISLAMIC AZAD UNIVERSITY TEHRAN MEDICAL SCIENCES - Ghasemi, Ziba (IJRDO - Journal of Applied Management Science, 2023)
Following the ever-increasing growth of technology, education also went towards using this development, and virtual education replaced traditional face-to-face education as a part of education. With the sudden outbreak of the Covid-19 pandemic, in many countries of the world, virtual education has completely replaced face-to-face education, and the opinion of users is crucial for the continuation of this type of education, at least as a part of the educational system.Method: In this study, the opinions of users of virtual education were investigated in two parts, teachers and learners in Tehran Islamic Azad University of Medical Sciences. Results: In general, users were satisfied with virtual training and believed that this type of training is economical and time-saving. Also, the students believed that the existence of the recorded videos of the class is beneficial in their understanding of the lessons and in the exams.Conclusions: the results of the opinions of users, both teachers and students, about the process of virtual education show the relative satisfaction of the participants in the survey, and in most cases, the sum of positive and neutral opinions is much more than the negative opinions.